EL USO DE LAS REDES SOCIALES Y EL DESEMPEÑO ACADÉMICO DE LOS ADOLESCENTES DE BÁSICA SECUNDARIA - JHON JAIRO VALENCIA ZULUAGA (Revista Ingeniería, Matemáticas y Ciencias de la Información)
Currently, ICTs are a powerful agent of change to redesign learning environments and teaching resources, allowingpedagogical models to be more flexible and qualified in terms of school functioning, the curriculum, the role of theteacher and the learning experiences that It is offered to the student. Therefore, the objective of the proposed researchtopic is the relationship between academic performance and the use of social networks by secondary school students.Morover, research reforms and educational policies located at current school as one that raises; the motivation,disinterest and apathy of the new generations compared to the training and education models that the traditional systemhas offered them, in this sense, the reality of the conceptual debate framed from the new information and communicationtechnologies, such as a theoretical corpus, education. The study was empirical with a quantitative approach, of descriptivetype, applied to the student population-major late-being a sample of 219 students of the San Vicente EducationalInstitution of the city of Guadalajara de Buga. The techniques and data collection instruments were the observation, thestructured survey, the questionnaire and the online form among others. In relation to the latter, a statistical analysis of thedata obtained was carried out, which allowed us to find a relationship between academic performance and time spent onsocial networks of secondary school adolescents.